Affinity‐based high‐resolution analysis of DNA binding by VASCULAR‐RELATED NAC‐DOMAIN7 via fluorescence correlation spectroscopy. (12th August 2019) - Tamura, Taizo; Endo, Hitoshi; Suzuki, Atsunobu; Sato, Yutaka; Kato, Ko; Ohtani, Misato; Yamaguchi, Masatoshi; Demura, Taku
Summary: VASCULAR‐RELATED NAC‐DOMAIN7 (VND7) is the master transcription factor for vessel element differentiation in Arabidopsis thaliana . To identify the cis ‐acting sequence(s) bound by VND7, we employed fluorescence correlation spectroscopy (FCS) to find VND7–DNA interactions quantitatively. This identified an 18‐bp sequence from the promoter of XYLEM CYSTEINE PEPTIDASE1 ( XCP1 ), a direct target of VND7. A quantitative assay for binding affinity between VND7 and the 18‐bp sequence revealed the core nucleotides contributing to specific binding between VND7 and the 18‐bp sequence. Moreover, by combining the systematic evolution of ligands by exponential enrichment (SELEX) technique with known consensus sequences, we defined a motif termed the Ideal Core Structure for binding by VND7 (ICSV). We also used FCS to search for VND7 binding sequences in the promoter regions of other direct targets. Taking these data together, we proposed that VND7 preferentially binds to the ICSV sequence. Additionally, we found that substitutions among the core nucleotides affected transcriptional regulation by VND7 in vivo, indicating that the core nucleotides contribute to vessel‐element‐specific gene expression. Furthermore, our results demonstrate that FCS is a powerful tool for unveiling the DNA‐binding properties of transcription factors. Significance Statement: We identified essential cis ‐acting sequence(s) that contribute to strict regulation of vessel‐element‐specific gene expression by VND7 NAC transcription factor, which provides critical insight for understanding the mechanisms of xylem vessel element differentiation. This manuscript also offers an experimental platform for quantitative binding assay using fluorescence correlation spectroscopy, combined with competition assay techniques, which allows us to characterize important nucleotides responsible for binding affinity between DNAs and proteins.